Investigation of using power lines as a communication environment - Kabalci, Yasin; Sorgucu, Uğur; Develi, Ibrahim (My University, 2010)
In this study, the historical development, channel models and problems of power line communication which is based on utilizing the energy lines as a transmission environment are investigated. The analyzed technology performed a rapid development and supplied high speed data transmission opportunities due to emerging very large scale integrated circuit designs and novelties in digital signal processing while it was applied in low speed data rates for controlling and pricing applications at the beginning. © 2011 Elsevier B.V., All rights reserved.
Haberleşme ortami olarak enerji hatlarinin kullaniminin i?ncelenmesi
2010 7th National Conference on Electrical, Electronics and Computer Engineering, ELECO 2010 -- Bursa -- 83834
Keywords: Channel Model; Data Rates; High-Speed Data Transmission; Historical Development; Low Speed; Power Line Communications; Power Lines; Rapid Development; Transmission Environment; Very Large Scale Integrated Circuit; Electric Lines; Signal Processing; Digital Integrated Circuits